Numerical modeling of icehouse and greenhouse sea-level changes on a continental margin: Sea-level modulation of deltaic avulsion processes. (January 2020) - Harris, Ashley D.; Covault, Jacob A.; Baumgardner, Sarah; Sun, Tao; Granjeon, Didier
Abstract: Sequence stratigraphic models emphasize changes in accommodation driven by relative sea level as a principal control on continental-margin development. Therefore, it has been hypothesized that there are differences in the volume and distribution of sand delivered to deep-water during the high-amplitude sea-level changes of icehouse settings versus the low-amplitude sea-level changes of greenhouse settings. Previous numerical modeling and field studies suggest an alternative hypothesis: that there would be minimal differences between each setting. Here, we used a three-dimensional numerical stratigraphic forward model to test the impact of greenhouse and icehouse sea-level changes on sand distribution in a passive margin setting. Model results were analyzed to evaluate the impacts of the rate and amplitude of relative sea-level changes on individual deep-water sand delivery events, total deep-water sand volumes, and sand distribution. Model results show that total deep-water sand volume is almost independent of the rate of relative sea-level change, which we attribute to the interaction of this sea-level change rate and the time required by the delta to reach a dynamic equilibrium state as a result of avulsion processes. However, there are major differences in the large-scale spatial distribution of sand between the icehouse and greenhouse conditions. The high amplitude sea-level changes in the icehouse model caused significant shelfal incision, which minimized deltaic avulsion processes and localized deep-water sedimentation. The relatively low amplitude sea-level changes in the greenhouse model allowed avulsion of the fluvial-deltaic system, thus causing more laterally extensive deep-water deposits. Our experimental results demonstrate that the rate of deep-water sand delivery is largest during periods of low sea level in both icehouse and greenhouse conditions, but show that there is a poor relationship between the rate of deep-water sediment delivery and the rate of sea-level change. We attribute both of these results to the nature of avulsion processes on the delta: more frequent avulsions of greenhouse deltas spread sediment across the shelf and limit sediment delivery to deep water until a dynamic equilibrium state is achieved, whereas the development of an icehouse incised valley locks the fluvial-deltaic system in place and localizes deep-water sedimentation. Moreover, our results indicate that the total volume of deep-water sand is controlled by the total sediment supply to the basin. These results provide a framework for the timing and quantity of continental-margin sedimentation and deep-water sediment delivery, with applications to sequence-stratigraphic interpretations. Highlights: Numerical stratigraphic forward models show icehouse and greenhouse settings deliver similar total deep-water sand volumes. The equilibrium state of the delta influences deep-water sand delivery rates. Model results show sea-level change can modulate fluvio-deltaic avulsion. Icehouse setting limited fluvio-deltaic avulsion compared to the greenhouse setting. Icehouse setting resulted in areally restricted deep-water sand deposition.